Bamboo thickets alter the demographic structure of Euterpe edulis population: A keystone, threatened palm species of the Atlantic forest - Rother, Débora Cristina [UNESP]; Rodrigues, Ricardo Ribeiro; Pizo, Marco Aurélio [UNESP] (Elsevier, 2016)
The rapid spread of bamboos can strongly affect forest structure by interfering plant regeneration and reducing local biodiversity. Considering that bamboos exert a negative influence on the plant community, our main goal was to investigate how this influence manifests at the population level. We compared the demographic structure of the threatened palm Euterpe edulis between bamboo and non-bamboo dominated patches within the Atlantic forest. In the study site, the native bamboo Guadua tagoara has created a marked patchiness and heterogeneity in the vegetation. Plots were set up randomly in bamboo and non-bamboo patches and the heights of all E. edulis individuals were measured. Data from canopy openness and litter depth were collected for both patches. Greater number of E. edulis was recorded in bamboo patches. However, frequency distribution of the height classes differed between patches revealing a predominance of seedling and sapling I classes in bamboo patches, in comparison to a more evenly distribution of height classes in non-bamboo patches. The canopy in bamboo patches was more open and the litter depth was thicker. Our analyses evidenced G. tagoara is functioning as a demographic bottleneck of natural population of E. edulis by arresting its later stages of regeneration and in high densities that bamboos may limit recruitment of this palm species.
Keywords: Arrested regeneration; Demographic bottleneck; Guadua tagoara; Palm heart; Recruitment limitation of later stages